Camrelizumab plus apatinib in patients with high-risk chemorefractory or relapsed gestational trophoblastic neoplasia (CAP 01): a single-arm, open-label, phase 2 trial. Issue 11 (November 2021) - Cheng, Hongyan; Zong, Liju; Kong, Yujia; Wang, Xiaoyu; Gu, Yu; Cang, Wei; Zhao, Jun; Wan, Xirun; Yang, Junjun; Xiang, Yang
Summary: Background: Treatment options for patients with high-risk chemorefractory or relapsed gestational trophoblastic neoplasia are scarce. The synergistic antitumour effect of immunotherapy and antiangiogenic drugs has been shown in many solid tumours. This phase 2 trial evaluated the activity and safety of camrelizumab (PD-1 inhibitor) plus apatinib (VEGF receptor inhibitor) in patients with high-risk chemorefractory or relapsed gestational trophoblastic neoplasia. Methods: This was a single-arm, open-label, phase 2 trial, done at a single tertiary health-care centre in Beijing, China. Women (18–70 years) with high-risk (International Federation of Gynecology and Obstetrics score ≥7) chemorefractory or relapsed gestational trophoblastic neoplasia who had received at least two lines of previously unsuccessful multidrug chemotherapy regimens and had an Eastern Cooperative Oncology Group performance status of 0–2 were eligible for inclusion. Patients received 4-week cycles of intravenous camrelizumab 200 mg every 2 weeks plus oral apatinib 250 mg once per day until disease progression or unacceptable toxicity. The primary endpoint was objective response rate assessed according to serum human chorionic gonadotrophin concentration. Activity and safety were analysed in all patients who received at least one dose of study drug. The study is ongoing, but recruitment is complete. The study is registered with ClinicalTrials.gov, NCT04047017 . Findings: Between Aug 7, 2019, and March 18, 2020, 20 patients enrolled; 19 (95%) were diagnosed with choriocarcinoma and one (5%) had placental site trophoblastic tumour. The median follow-up duration was 18·5 months (IQR 14·6–20·9). The objective response rate was 55% (95% CI 32–77); ten (50%; 95% CI 27–73) patients had complete response. The most common grade 3 treatment-related adverse events were hypertension (five [25%] patients), rash (four [20%] patients), neutropenia (two [10%]), leukocytopenia (two [10%]), and aspartate aminotransferase increase (two [10%]). One patient had a treatment-related serious adverse event (aspartate aminotransferase 19-times higher than the upper limit of normal). No grade 4 or 5 treatment-related adverse events were reported. Interpretation: Camrelizumab plus apatinib showed promising antitumour activity and acceptable toxicity and could be a salvage therapy option for the treatment of high-risk chemorefractory or relapsed gestational trophoblastic neoplasia. Immune checkpoint inhibitors combined with chemotherapy for heavily-treated patients and upfront use of camrelizumab plus apatinib for patients with high-risk gestational trophoblastic neoplasia are under investigation in phase 2 trials. Funding: National Natural Science Foundation of China, Jiangsu Hengrui Pharmaceuticals.